Poverty and wealth reporting of the German Government: Approach, lessons and critique - Christian Arndt; Jürgen Volkert (Institut für Angewandte Wirtschaftsforschung (IAW), 2009)
The Capability Approach has been adopted as a theoretical framework for official Poverty and Wealth Reports by the German government. For the first time, this paper provides information on the use of the Capability Approach in this reporting process to international readers. We show the background and processes that might have led the government to adopt Amartya Sen's Capability Approach as a framework for the reports and describe the Capability-related structure and main contents of the recent 3rd Poverty and Wealth Report. We also explain why the extension of the Capability Approach from poverty to wealth issues in German reports may be promising also for analyses of capability deprivation in general. Finally, we discuss major shortcoming and challenges of the reporting and end with a brief conclusion.
Keywords: 330; capability approach; poverty; wealth; affluent countries; Amartya Sen; Disparitätsmaß; Einkommensverteilung; Vermögensverteilung; Armut; Reichtum; Deutschland